Supporting Behaviour Management in Schools : Strategies Deployed by Head-Teachers - Mpendulo Ronald S'celo Magagula; Vitallis Chikoko (International Journal of Educational Development, 2025)
The head teacher's (hereinafter to be written HT) role is to foster a positive learning environment, essential for high-quality education. This qualitative research examined strategies used by HTs in three high schools in the Manzini region of Eswatini to promote effective behaviour management. One-on-one interviews were conducted with HTs from Mavalela (MV), Sidlamafa (SD), and Lomawa (LM) high schools, using pseudonyms for confidentiality. The analysis is based on the Transformational Leadership and Rogers’ Decisive Discipline Model frameworks, which explain leadership strategies and insights for creating respectful learning environments. Findings indicate that HTs prioritize respect, adherence to school policies, attendance, accountability for learner behaviour, teacher training, parental involvement, and providing necessary resources for teachers.